Intake, Rumen Degradation and Utilisation of Urea-Ammoniated Grass Hay by Kacang Goats as Affected by Supplementation of Sun-dried Fish or Fishmeal - Jelantik, IGN; Weibsjerg, MR; Madsen, J (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2012)
Six mature male Kacang goats were involved in an experiment arranged following a duplicate 3 x 3 latin square design. The objectives of this experiment was to study the effect of supplementation of dried fish as compared to fishmeal on intake, digestion, rumen environment and nitrogen use by the local meat type kacang goats maintained on urea-treated low quality grass hay. The treatments were G: goats were fed with ad libitum access of urea treated grass hay and 100 g/d putak, SDF: G plus 18.4 g sun dried fish, and FM: G plusÂ 19.7 g/d fishmeal. The supplement in SDF and FM was at equal CP level. Intake of urea treated grass hay tended to increase (P=0.08) with supplementation. Dry matter digestibility particularly that of CP was improved by supplementation. Rumen environment was slightly modified by supplementation. Rumen pH was reduced while ammonia concentration was increased. Rumen degradation of the treated grass hay did not differ when incubated in the rumen of goats with different diets. Nitrogen balance was significantly improved (P<0.05) by fishmeal supplementation. In all parameters measured in this experiment, the incremental effects did not differ between fishmeal type. This indicate that there is no further advantage of preparing fishmeal other than sun-drying in improving the utilisation of low quality urea-treated grass hay.Â Keywords: kacang goats, fishmeal, intake, digestion, utilisation, rumen environmentÂ Animal Production 14(2):77-86